Horizontal formwork design optimization & selection system using genetic algorithms - Ghowiba, Ramy Mohamed (AUC Knowledge Fountain, 2016)
Concrete works in most of the construction projects can be broken down into three main items; Formwork, Steel work, and concreting, No doubt, concrete works account for a large portion of construction projects budgets. As stated by Awad S. Hanna (1999), formwork material and labor can account for 40 to 60 percent of the cost of concrete works; however this percentage can vary slightly from country to another. That is why it is important to select an appropriate formwork system for a project; otherwise the project cost will be affected negatively. Formwork systems can be classified by their function into vertical and horizontal formwork systems, where horizontal formwork is used to support slabs, and beams, while the vertical formwork supports vertical elements like the columns. There have been attempts to optimize the design of formwork, and create a systematic approach for formwork selection based on expert opinion for both vertical and horizontal formwork systems. Despite the fact that expert based systems have been successfully applied to different projects; however, incorporating formwork design optimization with formwork selection system in one research or model is still not applied; especially for horizontal formwork systems. Therefore, the model developed in this research tackles the gap in literature, concerning the need for a formwork selection system that is not based on experts' opinion, and that can output a purchase cost and detailed quantity take-off with reasonable accuracy for the selected formwork system out of conventional wood formwork system, props system, frames system, and cuplock system for regularly shaped projects. In the research, a cost equation was developed, in order to compare all the formwork systems, while considering all the parameters affecting that selection. The model is developed using Microsoft Excel 2007 and Evolver 5.5(Palisade Decision tools), which is an excel add in that uses the Evolutionary algorithms (Genetic algorithm) optimization concept. In order to validate the model, the outputted designs were compared with real-life projects design calculation sheets prepared by Acrow Masr formwork company, while the quantity take-offs outputted from the model were compared to manual calculations, and yielded an accuracy of more than 90 percent. After the model output was validated, it was successfully applied to a high-rise construction project in Egypt, and the most appropriate formwork system for that project was outputted with a purchase cost, and design parameters. The formwork selection system was applied to an optimized low income housing plan developed in previous research; highlighting the appropriate formwork systems to be used based on the number of formwork uses per year; in addition to developing a complete formwork design drawings for these selected systems.